1998
DOI: 10.1021/om980506e
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Study of Ruthenium Silylene Complexes of the Type [(η5-C5Me5)(Me3P)2RuSiX2]+(X = Thiolate, Me, and Ph)

Abstract: Various ruthenium silyl complexes of the type Cp*(Me3P)2RuSiR3 (Cp* = η5-C5Me5; SiR3 = SiCl3 (1), Si(NMe2)3 (2), Si(SEt)3 (3), Si(S-2-Naph)3 (4), (5), Si(SCy)2Cl (6), and Si(SMes)2Cl (7, Mes = 2,4,6-trimethylphenyl)) were prepared by the reaction of Cp*(Me3P)2RuCH2SiMe3 with the appropriate silane HSiR3. Compound 3 was converted to the triflate Cp*(Me3P)2RuSi(SEt)2OTf (8) by the reaction of 3 with Me3SiOTf. Similar reactions produced Cp*(Me3P)2RuSi(NMe2)2OTf (13), Cp*(Me3P)2RuSi(NMe2)(OTf)2 (14), Cp*(Me3P)2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
42
0
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(48 citation statements)
references
References 110 publications
(74 reference statements)
5
42
0
1
Order By: Relevance
“…Cationic silylene complexes of the type [L n MSiR 2 ] can be prepared by removing an anionic substituent X À from the corresponding silyl complex [L n MSiR 2 X]. [12] Variation of substituents at the Group 14 element as well as variations of the metal unit meanwhile have led to a huge number of stable complexes with ligands which are analogous to carbenes. [13] As for the Fischer carbene complexes, the Dewar ± Chatt ± Duncanson model can be applied to explain the bonding (Scheme 3).…”
Section: Silylene Germylene Stannylene and Plumbylene Transition Mmentioning
confidence: 99%
“…Cationic silylene complexes of the type [L n MSiR 2 ] can be prepared by removing an anionic substituent X À from the corresponding silyl complex [L n MSiR 2 X]. [12] Variation of substituents at the Group 14 element as well as variations of the metal unit meanwhile have led to a huge number of stable complexes with ligands which are analogous to carbenes. [13] As for the Fischer carbene complexes, the Dewar ± Chatt ± Duncanson model can be applied to explain the bonding (Scheme 3).…”
Section: Silylene Germylene Stannylene and Plumbylene Transition Mmentioning
confidence: 99%
“…32 Late transition metal silylenoid complexes were first synthesized by exploiting the lability of silicon-triflate bonds (Scheme 7.2). [34][35][36][37] Tilley and coworkers reported that ruthenium silylenoid could be accessed in two steps from the silyl ruthenium cyclopentadienyl complex 8. Ethyl thiolate abstraction by trimethylsilyl triflate generated 9, which formed the silylenoid complex (10) on exposure to sodium tetraphenylborate.…”
Section: Introductionmentioning
confidence: 99%
“…?7 5 -Cyclopentadienyl (Cp) and rj 5 -pentamethylcyclopentadienyl (Cp*) derivatives 1 [3][4][5][6][7] as well as rj 6 -arene complexes 2-4 [8][9][10] adopt a three-legged piano stool geometry around ruthenium with legs composed of silyl and carbonyl or trimethylphosphine groups. The Ru -Si bond distance in trichlorosilyl complex 1 (Cp, L=Me 3 P) of 2.265 A, is consistent with a single bond.…”
Section: Compounds With Si -Ru Bondsmentioning
confidence: 99%
“…In spite of the fact, that the most direct probe of Ru -Si multiple bond character is the Ru -Si bond length, often the Μ -Si single-bond distances for transition metal silyl complexes are shorter than expected on the basis of covalent radii. The molecular structure of the cation in complex 44 [7] consists of a dimethylsilylene ligand that is planar at silicon and coordinated to Cp*(Me 3 P) 2 Ru fragment. The Ru = Si distance of 2.238 A is shorter than in other silylene complexes, however, it is longer as compared with compound 28 containing Ru -Si bond bridged by two hydrogen atoms.…”
mentioning
confidence: 99%